The Protection of Human Rights in Indonesian Constitutional Law after the Amendment of the 1945 Constitution of the Republic of Indonesia - Leli Tibaka; Rosdian Rosdian (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
The amendment to the 1945 Constitution of the Republic of Indonesia has shown progress in respecting, protecting and fulfilling human rights in Indonesia. It is proven from the advanced provisions that have set the human rights material, starting from the affirmation of fundamental rights, individual rights, social rights, solidarity rights, and even the assertion of rights included in the category of not-derogable rights in the Second Amendment to the 1945 Constitution. The urgency of the Constitution 1945 as written constitution due to its status as the ultimate instrument to determine a norm (law), action or government policy, so it will not violate human rights and constitutional rights of the citizens. Thus, the Constitution is an important instrument in term of guaranty and ensuring that human rights within the Republic of Indonesia are protected, even though the source of human rights is not actually derived from the State but naturally originated from natural law, whether its universal validity is either affirmed or not in the Constitution. It shows progress in the level of regulation and protection of human rights in Indonesia.Related to the guarantee of the protection of human rights, one of the important material of the 1945 Constitution of the Republic of Indonesia is the presence of a new judicial institution called the Constitutional Court, in addition to the Supreme Court. The existence of the Constitutional Court in Indonesia is an improvement in maintaining and upholding the Constitution and protecting human rights. Hence, the Constitutional Court referred to as “the Protector of Human Rights.” Protection of human rights is carried out through the exercise of authority as defined in Article 24C Paragraph (1) of the 1945 Constitution which is to review an Act against the Constitution, to judge on authority disputes of state institutions whose authorities are granted by the Constitution, to judge on the dissolution of a political party, and to judge on disputes regarding the result of a general election. Also, Article 24C Paragraph (2) obliges the Constitutional Court to render a judgment on the petition of the People’s Representative Council regarding an alleged violation by the President and the Vice President according to the Constitution. Keywords: Human Rights, Constitutional Law, Amendment to the Constitution.